2016
DOI: 10.1590/1982-43272665201607
|View full text |Cite
|
Sign up to set email alerts
|

College Adjustment as a Mediator Between Attention Deficit/Hyperactivity Disorder Symptoms and Work Self-Efficacy

Abstract: Abstract:Studies have addressed features of Attention Deficit/Hyperactivity Disorder (ADHD) in higher education, but the potential relationships between ADHD symptoms, dimensions of college adjustment and students' work self-efficacy remain scarcely explored. The aim of this study was to test a theoretical model in which the dimensions of college adjustment mediate the relationship between ADHD symptoms and work self-efficacy. Participants were 509 college students from two Brazilian public universities. Data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 39 publications
(47 reference statements)
0
3
0
9
Order By: Relevance
“…In the study by Oliveira and Dias (2014), the observed difficulties were a lack of options for extracurricular activities, missing family members, and responsibility for domestic activities. The qualitative comparison of the difficulties presented in these two studies as well as the negative correlation between the severity of ADHD symptoms and college adjustment (Oliveira et al, 2016) point to the need for further studies that compare whether there are qualitative and quantitative differences in the difficulties related to college adjustment faced by students with and without ADHD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the study by Oliveira and Dias (2014), the observed difficulties were a lack of options for extracurricular activities, missing family members, and responsibility for domestic activities. The qualitative comparison of the difficulties presented in these two studies as well as the negative correlation between the severity of ADHD symptoms and college adjustment (Oliveira et al, 2016) point to the need for further studies that compare whether there are qualitative and quantitative differences in the difficulties related to college adjustment faced by students with and without ADHD.…”
Section: Discussionmentioning
confidence: 99%
“…The way the main symptoms of ADHD may interfere in the academic life of students has been the focus of national and international studies (Advokat, Lane, & Luo, 2011;He & Antshel, 2017;Oliveira, Hauck-Filho, & Dias, 2016, Oliveira & Dias, 2015, Weyandt et al, 2013. Inattention, hyperactivity, and impulsivity may harm the organization of time and tasks (Rabiner, Anastopoulos, Costello, Hoyle, & Swartzwelder, 2008) and the establishment of interpersonal relationships, which results in academic and occupational impairments for students or adults with the disorder (Barkley, Murphy, & Fischer, 2010;He & Antshel, 2017, Pitts, Mangle, & Asherson, 2015.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As demais palavras são mencionadas apenas uma vez: Família, eficácia, bem-estar, jovem aprendiz, empregabilidade, dentre outras. Development, v. 9, n. 8, e814986206, 2020 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i8.6206 artigos que avaliaram se a autoeficácia na formação superior pode predizer a satisfação com a experiência acadêmica (Santos et al, 2019); compararam a autoeficácia na formação superior entre o primeiro e o segundo períodos letivos (Guerreiro-Casanova & Polydoro, 2011); verificaram a produção de conhecimentos sobre autoeficácia docente no contexto da Educação Especial no Brasil e no exterior, e, analisaram as pesquisas que investigaram os efeitos da formação sobre a autoeficácia de professores para a inclusão escolar de estudantes com deficiência, transtornos globais do desenvolvimento ou altas habilidades/superdotação (Martins & Chacon, 2019); investigaram a autoeficácia na formação superior e as vivências acadêmicas de estudantes cotistas e não cotistas de uma Universidade Pública (Sousa, Bardagi & Nunes, 2013); analisaram a relação entre autoeficácia para escolha profissional e adaptabilidade de carreira em estudantes do ensino médio, bem como verificar possíveis diferenças quanto à intenção ou não de participar em um processo orientação vocacional (Ambiel et al, 2018); exploraram os preditores de autoeficácia acadêmica em estudantes do ensino profissional em Portugal e no Brasil (Martins et al, 2018); testaram um modelo teórico no qual as dimensões do ajuste da faculdade mediam a relação entre Sintomas de TDAH e auto-eficácia no trabalho (Oliveira, Hauck-Filho & Dias, 2016).…”
Section: Cruzamentos Realizados Para Buscas Nas Bases De Dadosunclassified
“…Em revisão sistemática de literatura recente, verificou-se que estudantes universitários com TDAH claramente enfrentam dificuldades que seus pares sem o transtorno não encontram (Oliveira & Dias, 2015). Estudantes com TDAH tendem a apresentar menor bem-estar físico e psicológico, dificuldades de concentração e raciocínio, habilidades limitadas para estabelecer amizades e estudar, bem como menores níveis de autoeficácia profissional (Oliveira, Hauck-Filho, & Dias, 2016;Oliveira & Dias, 2017). As dificuldades de inibir e regular emoções negativas podem gerar problemas interpessoais e rejeição por colegas e professores (APA, 2013;Oliveira et al, 2016).…”
Section: Introductionunclassified